PRINCIPLE OF JUSTICE IN MANAGEMENT OF MARINE RESOURCES IN AREA CHARACTERIZED BY ISLANDS - Anwar, Arman; Irham, Muhammad (UI Scholars Hub, 2017)
Indonesia has eight provinces that are characterized as island regions, but in the setting of marine resource management authority is equated with the continental characterized provinces. Normative provisions apply but people in areas characterized by islands have been treated unfairly. In addition, the licensing system and the distribution of funds allocated as well as unfavorable framework in the implementation of regional autonomy. National government policies are deemed too oriented to the land where it is not appropriate to the needs of the regions. As a result, they are demanding to be no laws governing special about Islands Province. Government responded to amend the legislation on local government in accommodating the interests of the islands. The setting of the DAU and DAK, also provide more financial portion to the islands. It is expected to bring changes to the community. Implementation of regionally based local autonomy, excellence spatial and local potential is a determinant factor the success of regional development framework. Development process should be done based on diversity of various aspects that also needed a different treatment in each province. Thus, the question is whether the political law of the islands is done through changes and harmonization of the local governments law to provide a guarantee of justice so the demands for legislation that specifically regulates an island province is not matter any more. This study expected to find the values of justice and the foundation to be harmonized, so there exist principle of fairness in the management of marine resources in the waters of the area characterized by islands